Analysis of emergency department visits for all reasons by adults with depression in the United States - Hill, Tyler (BMC Emerg Med, 2020)
BACKGROUND: We aimed to characterize Emergency Department (ED) utilization and outcomes of patients with depression seeking emergency care for all reasons. METHODS: Using 2014–2016 ED data from the National Hospital Ambulatory Medical Care Survey, we investigated demographics, ED resource utilization, clinical characteristics, and disposition of patients with depression versus those without depression. RESULTS: Approximately 10,626,184 (11.4%) out of 92,899,685 annual ED visits were by patients with depression. ED patients with depression were mostly non-Hispanic White (74.0%) and were less likely to be male than patients without depression (aOR: 0.62; [95%] CI: 0.57–0.68). ED patients with depression were more likely to be admitted to the hospital (aOR: 1.50; CI: 1.38–1.63) than patients without depression. Among ED patients with depression, males were more likely than females to be seeking emergency care for psychiatric reasons (OR: 2.45; 95% CI: 2.10–2.87)) and to present with overdose/poisoning (OR: 1.46; CI: 1.03–2.05). CONCLUSIONS: We described the unique demographic, socioeconomic, and clinical characteristics of ED patients with depression, using the most comprehensive, nationally representative study to date. We revealed notable gender disparities in rates and reasons for admissions. The higher hospital and ICU admission rates of ED patients with depression suggests this population requires a higher level of emergency care, for reasons that remain poorly understood.